Figures de dialogisme et complémentation verbale dans des productions textuelles en FLE - Jeanneret, Thérèse (My University, 2002)
This paper deals with the practices of quotation in texts written by students of French as a foreign language at university. Quotation is considered as a writing process which is composed by a segmentation operation in the source text and an insertion operation in the target text. Both works of decontextualization and recontextualization require the mastery of the verbal complementation. Didactically, the paper emphasizes the heuristic function of quotation in text elaboration: a quotation should be a resource for writing.